Cutaneous Leiomyoma Localised on the Head and Dorsal Fin of a Goldfish, (Carassius Auratus) - A. Uma; N. Pazhanivel; G. Rebecca; S. Gangatharan; Ganesh Babu.S (The Indian Veterinary Journal, 2025)
Carassius auratus, is a popular freshwater ornamental fish of the family Cyprinidae is widely preferred by the hobbyists. A case of adult goldfish, Carassius auratus with cutaneous leiomyoma is reported in this study.  C. auratus with two round to spherical grey white coloured unencapsulated nodules measuring about 1.2 x 1.3 x 0.9 cm and 0.9 x 0.8 x 0.5 cm in size on the dorsal fin and near the mouth in the head region, respectively was examined. Histopathological examination of the nodules revealed interlacing bundles of neoplastic smooth muscle cells with cigar shaped nuclei with no mitotic figures. Based on the gross, histopathological and special staining examinations, the nodules were confirmed as leiomyoma.